Hierarchical ZnO nanorods/Ni(OH)2 nanoflakes for room-temperature, cheap fabrication of non-enzymatic glucose sensors. Issue 112 (23rd November 2016) - Strano, V.; Mirabella, S.
Abstract : Optimization of hierarchical nanostructures composed of Ni(OH)2 nanoflakes on ZnO nanorods (NRs) for inexpensive amperometric glucose sensing applications. Abstract : Hierarchical nanostructures composed of Ni(OH)2 nanoflakes on ZnO nanorods (NRs) are fabricated by a low-cost, fully chemical method at room-temperature. The morphological features of the ZnO NRs were varied (by changing the chemical bath deposition parameters) in terms of height and lateral size. ZnO NRs provide a large surface area substrate for the pulsed electrodeposition of nanostructured Ni(OH)2 . The correlation between the synthetic parameters, the final structure and the electrochemical behavior of Ni(OH)2 /ZnO nanostructures is investigated. The enzyme-free oxidation of glucose at the surface of electrodeposited Ni(OH)2 is demonstrated in 0.1 M NaOH, revealing that a proper choice of the electrodes fabrication conditions improves the glucose sensitivity up to 1.85 mA cm −2 mM −1, with a linear detection range of 0.04–2.10 mM. All the samples show a fast response time (less than 1 s), resistance in chloride solution, selectivity in the presence of common interfering electroactive species and excellent long-term stability. All these features, combined with the ease of the fabrication method, make Ni(OH)2 /ZnO nanostructures an ideal alternative for inexpensive amperometric glucose sensing applications.